Common Arterial Trunk Repair at the Red Cross War Memorial Hospital, Cape Town: A 20-year review of surgical practice and outcomes - Moodley, Allen (Division of General Surgery, 2024)
BACKGROUND: A description of the post-operative outcomes following Common Arterial Trunk (CAT) repair over 20 years before and following the transition to nonconduit repair. Primary outcomes were 30-day and overall, in-hospital mortality for paediatric patients who underwent CAT repair at Red Cross War Memorial Children's Hospital (RCWMCH). Secondary outcomes encompassed (a) Incidence of postoperative complications and (b) medium-term outcomes, including reinterventions, late deaths, and loss to follow-up. METHOD: A single-centre retrospective study of all consecutive patients who undertook the repair of CAT from January 1999 to December 2018 at RCWMH. Patients with an interrupted aortic arch or previous pulmonary artery banding were excluded. RESULTS: Fifty-four patients had CAT repair during the study period. Thirty-four (63.0%) patients had a conduit repair, and 20 (37.0%) patients had a non-conduit repair. There were 2 intraoperative deaths. Thirty-day in-hospital mortality was 22.2%. Overall, in-hospital mortality was 29.6%. Twenty-nine (55.8%) of fifty-two patients suffered a postoperative complication. A total of 38 patients were followed up post-hospital discharge with 11 patients (28.9%) lost to follow-up and 8 (21.1%) late mortalities observed. The actuarial survival for the conduit group was 77.5%, 53.4% and 44.5% at 6, 12 and 27 months respectively and non-conduit group was 58.6% at 6 months. The overall freedom from revision surgery between the conduit group and non-conduit group was 5 66.2% vs 86.5%, 66.2% vs 76.9% and 29.8% vs 64.1% at 1, 2 and 8 years respectively. CONCLUSIONS: No difference in postoperative mortality between the conduit and non-conduit repair. Reintervention rates were lower in the non-conduit group.